Acupuncture to Improve Patient Discomfort During Upper Gastrointestinal Endoscopy: Systematic Review and Meta-Analysis - Gao, Ning; Chen, Huan; Wang, Yang; Guo, Yufeng; Liu, Zhishun; Wang, Weiming (Frontiers in Medicine, 2022)
Background and aims: Severe discomfort during an upper gastrointestinal endoscopy (UGE) is often a stressful experience for patients undergoing the procedure. An increasing number of studies have shown that acupuncture may reduce discomfort during UGE. A systematic review in 2004 investigated the effect of acupuncture for gastrointestinal endoscopy, but these data have not been recently reviewed. Therefore, this study was conducted to evaluate the current evidence and provide up-to-date knowledge for clinical decision-making. Methods: Nine databases were searched from inception to June 2021. Eligible randomized controlled trials (RCTs) were included. The outcome data were synthesized where necessary, and risks of bias of included studies were assessed using RevMan V.5.3. Results: Twenty-three eligible RCTs with 3349 patients were identified. It was found that acupuncture plus topical pharyngeal anesthesia with lidocaine hydrochloride (TPALH) resulted in greater improvements regarding visual analog scale (VAS) scores and the incidence of nausea and vomiting (INV) when compared with TPALH alone. These results were consistent among studies of manual acupuncture, electroacupuncture, auricular-plaster, superficial needle (SFN) and acupressure. In the meta-analysis, SFN plus TPALH showed significant improvement of VAS scores compared to sham SFN plus TPALH (MD -1.11, 95% CI -1.52 to -0.70, P < 0.00001). Most of included studies did not report any side effects in their findings, and were of medium-to-high risk of bias. Conclusion: Acupuncture, as adjunctive therapy to TPA, may result in less patient discomfort than TPA alone. Findings from this review should be interpreted with caution due to the high heterogeneity identified. There is low-quality evidence supporting the use of acupuncture over sham. More rigorously designed RCTs are needed to inform clinical decision-making.